1996
DOI: 10.1021/jm960350p
|View full text |Cite
|
Sign up to set email alerts
|

Novel (R)-2-Amino-5-fluorotetralins:  Dopaminergic Antagonists and Inverse Agonists

Abstract: A series of secondary and tertiary N-alkyl derivatives of (R)-2-amino-5-fluorotetralin have been prepared. The affinities of the compounds for [3H]raclopride-labeled cloned human dopamine (DA) D2 and D3 receptors as well as [3H]-8-OH-DPAT-labeled rat hippocampal 5-HT1A receptors were determined. In order to selectively determine affinities for the high-affinity agonist binding site at DA D2 receptors, the agonist [3H]quinpirole was used. The intrinsic activities of the compounds at DA D2 and D3 receptors were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

1997
1997
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 45 publications
0
5
0
Order By: Relevance
“…Tentatively, this effect may be the result of so‐called inverse agonism (Kenakin, 1996). Recently, the assumption that D 2 receptors can indeed be the subject of inverse agonism has gained support also from studies by others (Giambalvo & Wagner, 1994; Hall & Strange, 1996a, b; Malmberg et al , 1996; Hall & Strange, 1997; Kozell & Neve, 1997). Notably, apart from the study by Giambalvo & Wagner (1994) using synaptoneurosomes prepared from rat neural tissue, all these examples of D 2 receptor‐mediated inverse agonism have been demonstrated in transfected systems characterized by an over‐expression of receptors.…”
Section: Discussionmentioning
confidence: 91%
“…Tentatively, this effect may be the result of so‐called inverse agonism (Kenakin, 1996). Recently, the assumption that D 2 receptors can indeed be the subject of inverse agonism has gained support also from studies by others (Giambalvo & Wagner, 1994; Hall & Strange, 1996a, b; Malmberg et al , 1996; Hall & Strange, 1997; Kozell & Neve, 1997). Notably, apart from the study by Giambalvo & Wagner (1994) using synaptoneurosomes prepared from rat neural tissue, all these examples of D 2 receptor‐mediated inverse agonism have been demonstrated in transfected systems characterized by an over‐expression of receptors.…”
Section: Discussionmentioning
confidence: 91%
“…Most of the dopamine antagonists have nonetheless been suggested to act as inverse agonists at the dopamine D 2 receptor (Hall & Strange, 1997; Strange, 1999), though these compounds, with the exception of (+)‐UH 232, could not be differentiated since they share a similar magnitude of inverse agonism. The weak amplitude of constitutive dopamine D 2 receptor activation (Malmberg et al ., 1996; Backlund Höök et al ., 1999; Choi et al ., 2000) as compared to other G protein‐coupled receptor systems (Daeffler & Landry, 2000) is perhaps one possible explanation for the apparent lack of differentiation between the intrinsic activity of these putative inverse agonists. We found clear differences in the activation profiles of both A371K and T372R D 2long receptor mutants by the partial agonists lisuride, (+)‐UH 232 and bromerguride.…”
Section: Discussionmentioning
confidence: 99%
“…Measuring forskolin‐stimulated cyclic AMP accumulation in transfected CHO‐K1 cells, Hall & Strange (1997) suggested that most antipsychotic drugs act as inverse agonists at both wild‐type D 2short and D 2long receptors. Also, these antagonists only weakly (<12%) inhibited basal [ 35 S]‐GTPγS binding to membranes expressing either the short or long isoform of the D 2 receptor (Malmberg et al ., 1996; Backlund Höök et al ., 1999; Choi et al ., 2000). One strategy to overcome this apparently weak amplitude of inverse agonist activity may be by introducing a facilitating mutation in the receptor sequence.…”
Section: Introductionmentioning
confidence: 99%
“…Comparing binding affinities (Table 1) at different D 2 -like receptor subtypes, dopamine showed higher affinity at human D 3 over D 2 (K i hD 2 /K i hD 3 = 2-43), but highest affinity at D 4 . Data for binding affinities showed high variations with different cell systems and screening conditions, e.g., K i = 13-240 nM hD 3 (Dörfler et al, 2008;Gerlach et al, 2003;Malmberg et al, 1996;Sautel et al, 1995) and K i = 0.8-25 nM rD 3 (Chio et al, 1994;Sokoloff et al, 1990).…”
Section: Receptor Agonistsmentioning
confidence: 99%